Gross Biometrical Studies on Pectoral Girdle of Small Indian Kite (Milvus migrans govinda) - Sharma, Aarti; Dubal, S. C. (Indian Journal of Veterinary Anatomy, 2016)
The study was conducted on the pectoralgirdle of six adult kites (Milvus migrans govinda). The skeleton of the pectoral girdle of the small Indian kite consisted of scapula, coracoid and clavicle.The shape index of scapula was 12.5 ± 0.005%. The mean value of the distance between the proximal ends of clavicle was 2.71 ± 0.07 cm. Thecoracoid was the strongest and the shortest bone of the pectoral girdle and the mean value of the weight of the coracoid was 0.891 ± 0.0282 g. The mean value of the area of the foramen triosseum was 0.36 ± 0.02 cm2.